Historical overview of cranial bone implants: own material or artificial prostheses - short review - Zygmunt Siedlecki; Fasi Ahamad Shaik; Karol Nowak; Sebastian Grzyb; Maciej Śniegocki (Kazimierz Wielki University, 2021)
We present a brief report on the different types of skull bone prostheses used in cranioplasty. Skull defects, most often resulting from severe head injuries, have been known since the times of Ancient Egypt. Ethnographic reports indicate that at that time the skull defects were restored with golden plates. In the following centuries of medical development, especially in modern centuries, cranioplasty has been performed more widely. Cranioplasty began to be performed also in defects after craniectomy. Such craniectomies have been performed for treatment brain hemorrhages, strokes, tumors with severe edema. A common dilemma is whether artificial prostheses are better or own bone material. We present a brief historical overview and the actual state based on the procedures performed in our neurosurgical department in Collegium Medicum in Bydgoszcz.